Efficient methods for high quality merging of spatial audio streams in Directional Audio Coding - Del Galdo, Giovanni; Pulkki, Ville; Kuech, Fabian; Laitinen, Mikko Ville; Schultz-Amling, Richard; Kallinger, Markus (126th Audio Engineering Society Convention 2009, 2009)
Directional Audio Coding (DirAC) is an efficient technique to capture and reproduce spatial sound. The analysis step outputs a mono DirAC stream, comprising an omnidirectional microphone pressure signal and side information, i.e., direction of arrival and diffuseness of the sound field expressed in the time-frequency domain. This contribution proposes efficient methods to merge multiple mono DirAC streams to allow a joint playback at the reproduction side. The problem of merging two or more streams arises in applications such as immersive spatial audio teleconferencing, virtual reality, and online gaming. Compared to a trivial direct merging of the decoder outputs, the proposed methods are more efficient as they do not require any additional synthesis step. From this it follows the benefit that the loudspeaker setup at the reproduction side does not have to be known in advance. Simulations and listening tests confirm the absence of any artifacts and that the proposed methods are practically indistinguishable from the ideal merging.
CRIS-Team Scopus Importer:2025-11-10